Pemustaka Zaman Now Versus Peprustakaan Zaman Now - Supardi Supardi (Institut Agama Islam Negeri Salatiga, 2018)
This 21st century information age Information and Communication Technology (ICT) becomes an integral part of our lives, especially educational institutions. All, including racing libraries to integrate ICTs to build and empower their knowledge-based academic community to compete in the global era. In this paper is presented about the condition of society in general that has made information and communication technology into the needs of every human being in every circumstance. The community's dependence on information and communication technology has changed the way people live and culture in everything. Information and communication technology has become a lifestyle, a human lifestyle. In this paper also presented some examples of information and communication technology applications in various fields including in the field of libraries. In response to that the library must appear by applying information technology and communication in providing services to users. In this paper also conveyed the importance of library organizers (librarians) to equip themselves with the skills and knowledge of information and communication technology in the field of library